Physiological Aspects of Germination and Early Seedling Establishment of Pleurotus sajor-caju Glyceraldehyde-3-Phosphate Dehydrogenase Expressing Transgenic Rice in Saline Environment - Siddiqui, Zamin Shaheed; Lee, Gang-Seob; Cho, Woosuk; Jeong, Mi-Jeong; Park, Soo-Chul; Kwon, Taek-Ryoun; Zulfiqar, Faisal; Umar, Muhammad; Abideen, Zainul; Uddin, Zaheer; Ansari, Hafiza Hamna; Wajid, Danish; et al. (Frontiers in Plant Science, 2022)
GPD encodes glyceraldehyde-3-phosphate dehydrogenase enzyme involved in sugar mobilization, particularly glycolysis and gluconeogenesis. The objective of this study was to determine physiological aspects of germination and early seedling establishment of PsGPD (Pleurotus sajor-caju glyceraldehyde-3-phosphate dehydrogenase) expressing transgenic rice (T5) against different salt concentrations. The T5 line that carried 2 copies of T-DNA and had the highest level of PsGPD expression was used in the investigation. Final germination percentage, amylase activity, reducing sugar accumulation, and chlorophyll biosynthesis were comparatively higher in PsGPD expressing transgenic rice against elevating saline conditions. A slow-paced conversion of porphyrin’s precursors was seen through the matrix model and further elaborated by a graphical model. A sustained level of porphyrin was observed in PsGPD expressing transgenic rice. These data were concurrent with the relative gene expression and thermal imaging (thermography) of PsGPD expressing transgenic rice against salt stress. Morphological attributes also favored the salt tolerance exhibited by PsGPD transformed rice.